2017
DOI: 10.1038/s41598-017-16605-w
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of layered perovskite Sr2TiO4 for improved CO2 photoreduction with H2O to CH4

Abstract: Layered perovskite Sr2TiO4 photocatalyst was synthesized by using sol-gel method with citric acid. In order to increase the surface area of layered perovskite Sr2TiO4, and thus to improve its photocatalytic activity for CO2 reduction, its surface was modified via hydrogen treatment or exfoliation. The physical and chemical properties of the prepared catalysts were characterized by X-ray diffraction, high-resolution transmission electron microscopy, elemental mapping analysis, energy-dispersive X-ray spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Considering the peaks appeared at 31.3 , 32.6 , 42.52 , 43.48 , 46.74 , 55.38 , 57.24 , and 65.08 , the Ruddlesden-Popper structure was successfully generated as a result of the reduction process with an indication of n ¼ 1 with a tetragonal structure. [32] Furthermore, any impurity phases such as La 2 O 3 and SrO, which could be formed undesirably during the exsolution process, were not observed. After its exposure to an oxidizing atmosphere, it can be observed that the CoFe-R.P.LSCF could be returned to the original LSCF without any formation of impurity phases; this result suggests that the LSCF has fairly good reversibility between two structures and reveals the possibility that LSCF can be used as a symmetric SOFC.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the peaks appeared at 31.3 , 32.6 , 42.52 , 43.48 , 46.74 , 55.38 , 57.24 , and 65.08 , the Ruddlesden-Popper structure was successfully generated as a result of the reduction process with an indication of n ¼ 1 with a tetragonal structure. [32] Furthermore, any impurity phases such as La 2 O 3 and SrO, which could be formed undesirably during the exsolution process, were not observed. After its exposure to an oxidizing atmosphere, it can be observed that the CoFe-R.P.LSCF could be returned to the original LSCF without any formation of impurity phases; this result suggests that the LSCF has fairly good reversibility between two structures and reveals the possibility that LSCF can be used as a symmetric SOFC.…”
Section: Resultsmentioning
confidence: 99%
“…Instead a pattern which is indicative for fluorinated RP-type phases with significant shifts of reflections to higher angles as well as splitting of some of the reflections (see Figure 2) is observed. This pattern could be indexed in the monoclinic crystal system with lattice parameters of a = 13.6284(3) Å, b = 5.99217(10) Å, c = 5.92016(11) Å, and β = 90.886(2)° with additional indication for a C-centered cell, which is in contrast to the tetragonal symmetry found for the starting material (a = 4.17797(5) Å, and c = 12.97255 (19) Å; please note that also lower symmetries have been reported for LaBaInO4 with a small orthorhombic distortion and space group Pbca, a = 12.933(3) Å, b = 5.911(1) Å, c = 5.905(1) Å 23,36 ). In addition to this phase, another phase with a broader reflection was observed at ~ 28° 2θ, which is, according to our experience, indicative for higher fluorine content RP-type phases with a larger c lattice parameter (c = 16.502(12) Å).…”
Section: Labaino3f2mentioning
confidence: 94%
“…Such substitutive topochemical fluorination reactions, can be performed with fluoride-containing polymers such as polyvinylidene difluoride (PVDF, (CH2CF2)n) 17,18 . A few RP-type materials such as strontium titanate (Sr2TiO4), lithium calcium-tantalates (Li2CaTa2O7, A(Ca/Sr/Ba)La4Ti4O15), and strontium tin oxides (Sr2SnO4) have been reported to be efficient hydrogen evolution catalysts with bandgap values of 3.52 eV, 4.36 eV, 4.6 eV, respectively 4,8,10,19 . Limitations are imposed by the wide bandgap, making them only active in UV light which is not sustainable to harvest solar energy.…”
mentioning
confidence: 99%
“…Acidic sites on the surface of photocatalysts are beneficial for CO 2 reduction as well as for specific molecular bonding, which depends on their adequate separation of photogenerated charge carriers. [ 326 ] Proper surface acid sites grown on the Nb 2 O 5 photocatalyst can control the activity and selectivity of CO 2 conversion. [ 327 ] It was proved that CO and HCOOH were produced under high surface acidity, while low surface acidity tended to generate CH 4 .…”
Section: Surface Structure Engineeringmentioning
confidence: 99%